DIAGNOSTICO SOBRE A PRODUÇÃO E A OFERTA DE UNIDADES HABITACIONAIS DE INTERESSE SOCIAL EM ARACAJU - Sant'anna, Igor; Santos, Débora (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The large housing deficit in Aracaju, specifically for those families with a monthly income of up to 03 (three) minimum wages, has not been supplied in recent years. This article proposes, through literature review, documentary and field research, to identify the technical, economic and legal conditions that impose this production, as well as to quantify the production and supply of social housing in Aracaju, from the year 2000. The research identified the regions of social interest, the number of units offered and characterized the level of service, in relation to the urban infrastructure of these areas. It was possible to infer that the great majority of related enterprises were located in the most peripheral areas of the city, always in areas of low value added, with a great deficit of urban infrastructure, as well as the stagnation of the supply of new units of habiutation of social interest.